Enzymatic depolymerazation of lignin by laccases - Nor Hanimah, Hamidi (2013)
More than half of platform petrochemicals are aromatic, whereas the only large-scale, naturally-occurring, renewable source of aromatics is lignin. Chemical depolymerization of lignin requires extreme conditions, and results in extensive destruction of the aromatic rings and/or char formation. By contrast, enzymatic lignin depolymerization occurs under mild conditions with retention of the aromatic nuclei. Therefore, laccase from Agaricus bisporus (LAB) and from Trametes versicolor (LTV) with the mediator, ABTS (2,2'-azino-bis(3 ethyl benzthiazoline-6-sulphonic acid)) were used to depolymerize lignin (sodium lignosulphonate) under mild reaction conditions with the aim to obtain high concentrations of value-added chemicals. The depolymerization in the presence of LTV was higher than LAB, which resulted from the high catalytic activity of LTV. Lignin degradation resulted in formation of complex product mixtures. Therefore the products were fractionated and analyzed by different analytical techniques including GPC (for preliminary screening), HPLC and GCMS (for product characterization and quantification), and NMR (for fingerprint analysis). Products included guaiacol, vanillin, acetovanillone, vanillic acid, homovanillyl alcohol, phenol, 4- methylbenzaldehyde, catechol, p-toluic acid, 4-hydroxybenzaldehyde, tyrosol, isovanillin, and 3-hydroxy-l-( 4-hydroxy-3-methoxyphenyl) propan-1-one, and the total yield of monomers from lignin was 9.8 % in the presence of LTV. The parameters involved in the depolymerization process were optimized to increase the yield of monomers. The efficiency of laccase mediators -was also explored by the use of 2, 2,6,6-tetramethylpiperidin-l-yloxy (TEMPO), 1-hydroxybenzotriazole (HBT), Nhydroxyphthalimide (HPI) and violuric acid (VLA) in the depolymerization of sodium lignosulphonate. However, the catalytic depolymerization in the presence of these mediators was lower than ABTS. In order to improve the solubility of the substrate for the depolymerization process, screening of ionic liquids that are compatible with LAB was deployed in order to find laccase-friendly ionic liquids for further use in lignin depolymerization. The study has found [C4mim] [L-tartrate] as the best ionic liquid tested, that increased the activity of LAB by 90 %. In conclusion, enzymatic depolymerization of lignin offers a greener process than the chemical methods, and also provides a more efficient method to obtain monomers of valuable specialty chemicals under mild reaction conditions.